Adaptation of International Accounting Standards: Case of Portugal - Saraiva, Helena (2018)
This chapter aims to present the results of a broad analysis about the process of accounting standardization in Portugal in order to frame the current situation and the different levels of standardization that characterize it. The methodology followed involves a broad revision of the literature and content analysis on various papers and texts as well on documents directly related with the study topic. It concludes with the identification and characterization of the current levels of accounting standardization and makes reference to the likely scenario of this regulatory framework in the short term. The objective is to understand how the evolution of accounting standards in Portugal has evolved, what the current situation is and its likely evolution in the near future. The chapter is also aimed at contributing to the understanding of the process of adaptation of international accounting standards to the Portuguese reality.